GAMBARAN FAKTOR RISIKO GAGAL GINJAL KRONIS PADA PASIEN HIPERTENSI BERDASARKAN LAMA MENDERITA HIPERTENSI DI RSUP FATMAWATI TAHUN 2020 - Amastia Ikayuwandari, (2020)
Basic Health Research Data in 2018 shows the high prevalence of hypertension in Indonesia, especially in South Jakarta, which is 10.92%. Hypertension is the most significant risk factor for the development of chronic kidney failure. However, chronic kidney failure is a multifactorial disease which requires more than one factor to cause symptoms of chronic kidney failure. The purpose of this study was to determine the description of risk factors for chronic kidney failure in hypertensive patients based on the length of hypertension at Fatmawati General Hospital in 2020. This study used a cross sectional study design. The sampling technique used was purposive sampling with 87 respondents. The results of this study using the chi-square test showed that there were no differences in risk factors for adherence to taking antihypertensive drugs (p = 0.160), other comorbidities: diabetes mellitus (p = 1,000), chronic glomerulonephritis (p = 1,000), polycystic kidney disease (p = 0.195), obstructive nephropathy (p = 1,000), chronic pyelonephritis (p = 0.096), obesity (p = 0.449), smoking (p = 0.184), daily fluid consumption (p = 0.460), alcohol consumption (p = 0.696), and consumption of energy supplement drinks (p = 0.456) with hypertension ≥ 10 years and <10 years.